2017
DOI: 10.11646/zootaxa.4362.1.9
|View full text |Cite
|
Sign up to set email alerts
|

Description of a new species of Bothynus Hope from Argentina and Bolivia (Coleoptera: Scarabaeidae: Dynastinae)

Abstract: A new species of Bothynus Hope, 1837 (Coleoptera: Scarabaeidae: Dynastinae: Pentodontini) is described from the eastern Andes in South America. The new species is unique in the genus for having the elytra and part of the pronotum covered with small setae.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 533 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…Specifically, the forest habitat types of the four species are detailed below. D. maya occurs in tropical and montane broadleaf rainforests from Guatemala, Honduras and the Mexican state of Chiapas (Figure 1a), with the majority of occurrence data located at 500–1500 m above sea level (Hardy, 2003; Huang, 2017; Morón, 2009; Ratcliffe et al., 2013; Ratcliffe & Cave, 2006). Recently, D. maya has been observed in temperate mixed forests in the Mexican states of Oaxaca (Moctezuma & Sánchez‐Huerta, 2018) and Puebla (García‐Morales et al., 2022).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, the forest habitat types of the four species are detailed below. D. maya occurs in tropical and montane broadleaf rainforests from Guatemala, Honduras and the Mexican state of Chiapas (Figure 1a), with the majority of occurrence data located at 500–1500 m above sea level (Hardy, 2003; Huang, 2017; Morón, 2009; Ratcliffe et al., 2013; Ratcliffe & Cave, 2006). Recently, D. maya has been observed in temperate mixed forests in the Mexican states of Oaxaca (Moctezuma & Sánchez‐Huerta, 2018) and Puebla (García‐Morales et al., 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, the forest habitat types of the four species are detailed below. D. maya occurs in tropical and montane broadleaf rainforests from Guatemala, Honduras and the Mexican state of Chiapas (Figure 1a), with the majority of occurrence data located at 500-1500 m above sea level (Hardy, 2003;Huang, 2017;Morón, 2009;Ratcliffe et al, 2013;Ratcliffe & Cave, 2006) We showed that D. grantii and D. hyllus, which are associated with temperate-to-subtropical oak-pine forests, reached their peaks in effective population sizes during LIG. Previous studies based on palaeoclimatic data have revealed that the LIG was a time when the global climate was as warm or warmer than at present, where temperate mixed forests were in areas with similar vegetation as at present (Kukla et al, 2002), which corroborates the estimated effective population size in D. grantii and D. hyllus.…”
Section: Reference Genomes For Biological Conservationmentioning
confidence: 94%